The usage of McDonald application among UiTM Terengganu students / Nur Shafika Atasha zukri Kini and Ilya Fiona Syafika Kamarulbahrin - Zukri Kini, Nur Shafika Atasha; Kamarulbahrin, Ilya Fiona Syafika (2019)
The purpose of this research is to identify effectiveness of the McDonalds mobile application among the students in UiTM Dungun and to identify the satisfaction of UiTM students in using the applications. The mobile apps have been known to the world market and most of the foodservice establishment also has their own apps to make the sales market. The organizations are designed their own in-app purchases to increase their sales and do the promoting of their products and services through the mobile apps. The factors that have been analysed in this study are the effectiveness and satisfaction of students by using the mobile applications in then- everyday life. This research was done by conducting a survey and the questionnaire were distributed to the students in UiTM Dungun. The data were analysed by Statistical Package for the Social Science (SPSS). The results were analysed by using frequency analysis. The findings and interpretation of the research are identified in chapter four. From the results, it shows that its effective and satisfied the respondents that using the mobile applications. In conclusion, this research can give some valuable information to the researcher, organizations and the reader which is useful for basic knowledge. Hopefully it can attract the society to grab chance in using the mobile applications that can make their everyday life easier.